2005
DOI: 10.1007/s00167-005-0635-8
|View full text |Cite
|
Sign up to set email alerts
|

Tendoscopic debridement for stage I posterior tibial tendon dysfunction

Abstract: Our objective is to assess whether the tendoscopic synovectomy is effective to control the stage I posterior tibial tendon dysfunction. Our study is a retrospective one. The participants, six patients with stage I posterior tibial tendon dysfunction, were treated with tendoscopy with synovectomy for the past 3 years. The results show that this is a safe procedure and we could achieve similar effectiveness as the traditional open procedure. There was no complication found. None of our patients have progressed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 14 publications
0
52
0
Order By: Relevance
“…The presence of chronic peroneal tendon subluxation or dislocation and peroneal tenosynovitis presents with chronic peroneal pain and swelling [14]. Peroneal tendon injuries or degeneration especially if Clinical studies related to tendoscopic management of other tendon sheaths have been already published for stage 1 tibialis posterior tendon dysfunction [2,18] and for toe flexors [11]. Authors of both studies concluded that tendoscopic management is an effective and minimal invasive surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of chronic peroneal tendon subluxation or dislocation and peroneal tenosynovitis presents with chronic peroneal pain and swelling [14]. Peroneal tendon injuries or degeneration especially if Clinical studies related to tendoscopic management of other tendon sheaths have been already published for stage 1 tibialis posterior tendon dysfunction [2,18] and for toe flexors [11]. Authors of both studies concluded that tendoscopic management is an effective and minimal invasive surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Open exploration of the tendon usually requires extensive soft tissue dissection. Different tendoscopies of the foot and ankle have been described before [2][3][4][5]. We describe a tendoscopic approach to deal with the flexor hallucis tendon pathology.…”
Section: Introductionmentioning
confidence: 99%
“…27 Khazen and Khazen performed PTT tendoscopies in nine patients with stage I PTT dysfunction, with pain improvement in eight patients. 28 Lui reported on the use of endoscopic-assisted PTT reconstruction for stage II dysfunction.…”
Section: Resultsmentioning
confidence: 99%